Efectos de la implementación de la facturación electrónica en Colombia estudio de caso comercializadora escalar S.A.S (2021)
The implementation of Electronic Invoicing in Colombia was a radical change from the traditional invoicing system to electronic invoicing, which was carried out in order to eliminate the risk of manipulation and loss of physical documentation